2014
DOI: 10.3762/bjnano.5.253
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory and cytotoxic response to nanoparticles in precision-cut lung slices

Abstract: SummaryPrecision-cut lung slices (PCLS) are an established ex vivo alternative to in vivo experiments in pharmacotoxicology. The aim of this study was to evaluate the potential of PCLS as a tool in nanotoxicology studies. Silver (Ag-NPs) and zinc oxide (ZnO-NPs) nanoparticles as well as quartz particles were used because these materials have been previously shown in several in vitro and in vivo studies to induce a dose-dependent cytotoxic and inflammatory response. PCLS were exposed to three concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Details on the experiments with precision-cut lung slices (PCLS) are given in [126]. Details on the triple-cell 3D culture are described in [125,127129].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on the experiments with precision-cut lung slices (PCLS) are given in [126]. Details on the triple-cell 3D culture are described in [125,127129].…”
Section: Methodsmentioning
confidence: 99%
“…b Significant, but weak increase in LDH release after incubation for 4 h and 24 h. No increase in CXCL-1 or TNF-α protein as determined by ELISA [126]. c Significant increases in BALF LDH, total protein, and cytokine levels as well as in BALF neutrophil numbers 24 h after intratracheal instillation of 250 µg silver nanoparticles [124].…”
Section: Reviewmentioning
confidence: 99%
“…Comparison of ex vivo and in vivo gut exposure to TiO 2 NM show similar modes of translocation and localization in the epithelium of both models . Rat, mouse, or human precision‐cut lung slices are used to assess toxicant effects on the respiratory tract, such as cytotoxicity, genotoxicity, altered protein content, oxidative stress, apoptosis, cytokine release, and histological changes . The use of ex vivo methods for NM is still uncertain due to susceptibility to interferences, highly variable results, and an inability to determine appropriate dose metrics that relate to in vivo exposure .…”
Section: Existing and Emerging Methods Used As Part Of An Atsmentioning
confidence: 99%
“…The use of ex vivo methods for NM is still uncertain due to susceptibility to interferences, highly variable results, and an inability to determine appropriate dose metrics that relate to in vivo exposure . Ex vivo methods may be useful for prioritization and ranking of NM toxicity but further method optimization is likely needed to address reproducibility, false positives, false negatives, and to better understand the limitations of the system . Despite these limitations, the use of other ex vivo methods for NM still provides critical information on end points such as distribution, penetration, and uptake, and remains a promising method for testing broader types of NM.…”
Section: Existing and Emerging Methods Used As Part Of An Atsmentioning
confidence: 99%
“…Although most studies have focused on aspects of pharmatoxicology (44,45), some recent publications have proven that PCS-based approaches are highly relevant for the risk assessment of nanomaterials and xenobiotics in general, in terms of inflammation, organ injury and sensitization (46)(47)(48). A recently published study showed, however, that the system might only be useful for ions released from nanoparticles or soluble substances since it was observed that the silver nanoparticles did predominantly attach at the cut surfaces of the PCS from lung tissues ( Figure 1C) but could hardly penetrate into deeper regions (49).…”
Section: Ex Vivo Tissue Preparation: Bringing In Vivo Tissue Into Petmentioning
confidence: 99%